Analisis Faktor Pendukung dan Penghambat Implementasi Perda Kota Cimahi Nomor 20 Tahun 2018 Tentang Perlindungan dan Pemenuhan Hak Penyandang Disabilitas - Risca Dara Mutiara; Cecep Darmawan; Kanigara Hawari (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
People with disabilities still face various barriers in exercising their equal rights, including in accessing public facilities and tourism sites. This study aims to analyze the factors that support and hinder the implementation of Cimahi City Regulation No. 20 of 2018 on the Protection and Fulfillment of the Rights of Persons with Disabilities, particularly at tourist attractions in Cimahi City. The approach used is qualitative, employing a case study method to explore the phenomenon of policy implementation in depth using various data sources. The research findings indicate that supporting factors include strong legal legitimacy, the local government’s political commitment, coordination across Local Government Agencies (LGAs), the use of social media for outreach, and the involvement of the disability community in the planning process. Meanwhile, inhibiting factors include budget constraints, suboptimal accessibility facilities, a weak database system for disability needs, uneven public outreach, low empathy among tourism managers, and weak enforcement of sanctions. This study implies the need for strengthened oversight, optimization of resources, massive legal education, and a shift in mindset to achieve substantive inclusivity.